Antithrombotic Effect of Artemisia princeps Pampanini Extracts in Vitro and in FeCl3‐Induced Thrombosis Rats. Issue 10 (11th September 2019) - Kim, Kyeong Jin; Kim, Min Seo; Seok, Pu Reum; Shin, Jae‐Ho; Kim, Ji Yeon
Abstract: Extracts of several plants possess antithrombotic effects. Herein, we examined the antithrombotic effects of different extracts of Artemisia princeps Pampanini prepared using distilled water, hot distilled water, 70% ethanol, or subcritical water. The antithrombotic effects were determined using a co‐culture system consisting of tumor necrosis factor‐alpha (TNF‐α)‐treated EA.hy926 cells and THP‐1 cells. In addition, the coagulation time of plasma collected from healthy volunteers was evaluated in terms of the prothrombin time and activated partial thromboplastin time. A carotid arterial thrombosis model was induced by ferric chloride in Sprague Dawley rats. The rats were treated with either sterile water or three different doses of the subcritical water extract for 2 weeks. The thrombus weight, gene expression of cell adhesion molecules, and histological characteristics were assessed. The results of in vitro studies revealed a significant inhibition in the adhesion of monocytes to EA.hy926 cells stimulated by TNF‐α in the subcritical water extract‐treated group. We also observed considerable suppression of the occlusion and mRNA expression of cell adhesion molecules in the in vivo experiments. This study suggests that Artemisia princeps Pampanini may have the potential to improve blood coagulation.